High‐resolution sodium imaging using anatomical and sparsity constraints for denoising and recovery of novel features. Issue 2 (25th March 2021) - Zhao, Yibo; Guo, Rong; Li, Yudu; Thulborn, Keith R.; Liang, Zhi‐Pei
Abstract : Purpose: To develop and evaluate a novel method for reconstruction of high‐quality sodium MR images from noisy, limited k‐space data. Theory and Methods: A novel reconstruction method was developed for reconstruction of high‐quality sodium images from noisy, limited k‐space data. This method is based on a novel image model that contains a motion‐compensated generalized series model and a sparse model. The motion‐compensated generalized series model enables effective use of anatomical information from a proton image for denoising and resolution enhancement of sodium data, whereas the sparse model enables high‐resolution reconstruction of sodium‐dependent novel features. The underlying model estimation problems were solved efficiently using convex optimization algorithms. Results: The proposed method has been evaluated using both simulation and experimental data obtained from phantoms, healthy human volunteers, and tumor patients. Results showed a substantial improvement in spatial resolution and SNR over state‐of‐the‐art reconstruction methods, including compressed sensing and anatomically constrained reconstruction methods. Quantitative tissue sodium concentration maps were obtained from both healthy volunteers and brain tumor patients. These tissue sodium concentration maps showed improved lesion fidelity and allowed accurate interrogation of small targets. Conclusion: A new method has been developed to obtain high‐resolution sodium images with good SNR at 3 T. The proposed method makes effective use of anatomical prior information for denoising, while using a sparse model synergistically to recover sodium‐dependent novel features. Experimental results have been obtained to demonstrate the feasibility of achieving high‐quality tissue sodium concentration maps and their potential for improved detection of spatially heterogeneous responses of tumor to treatment.